2010
DOI: 10.1007/s00432-010-0904-x
|View full text |Cite
|
Sign up to set email alerts
|

CCND1 G870A polymorphism and cervical cancer risk: a case–control study and meta-analysis

Abstract: The G870A polymorphism in CCND1 may not contribute to the etiology of cervical cancer in Chinese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
2
7
0
2
Order By: Relevance
“…In 2011, Ni et al reported the first meta-analysis on the association between CCND1 G870A polymorphism and cervical cancer risk [17]. Only five studies were included in their review.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Ni et al reported the first meta-analysis on the association between CCND1 G870A polymorphism and cervical cancer risk [17]. Only five studies were included in their review.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported an association between the Cyclin D1 polymorphism (A870G) and an increased risk of developing various solid tumors [20][21][22][23][25][26][27][28][29][31][32][33][34][35][36][37][38][39][40][41][42][43]. But this association might be ethnic different.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the A allele appears to increase cancer risk in Chinese populations for breast (38) and bladder cancer (39), indicating that A allele carriers may produce an elevated cancer risk. However, a meta-analysis conducted on cervical cancer (40) failed to show this marked association. Similarly, no evidence supports the association of CCND1 genetic variation with head and neck cancer (41) in a recently published meta-analysis, of which the data were combined as head and neck cancer rather than oral carcinoma, and two important studies (29,32) on oral cancer that met the inclusion criteria were ignored.…”
Section: Discussionmentioning
confidence: 99%